Perbedaan Kosakata Dialek Melayu di Desa Betung dengan Desa Kesuma Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Rieke Nur Safitri; Auzar; Hermandra (GERAM: Gerakan Aktif Menulis, 2021)
This research was motivated by the existence of interest and curiosity about why two villages are very close in the distance, which use the same language but have many differences in the use of vocabulary used in speaking in the daily life of the speech community. Using different vocabulary in the spoken community in Betung and Kesuma villages raises questions about the differences in vocabulary and what factors influence these differences. The research objective was to describe the difference in vocabulary between the two villages. This research is expected to become a reference for similar research and as material to add insight. This research uses vocabulary theory, language variation, and technique. This research is qualitative research using the descriptive analysis method. Data were collected using the method of observation, interviews, proficient listening, and note-taking techniques. The collected data is then reduced, displayed, concluded. Based on the research process that the author has carried out, it was found that the results of the study were the differences in the vocabulary of the Malay dialect used by the speech community between Betung Village and Kesuma Village. The author found 71 differences in vocabulary that will be analyzed based on semantic differences, namely synonyms. The author also found six differences in vocabulary that will be analyzed based on semantic differences, namely homonyms. The author also obtained the study results, namely the factors that influence the vocabulary used by the spoken community in Betung Village and Kesuma Village.